Fast-scanning photoacoustic microscopy with a side-looking fiber optic ultrasound sensor - Liang, Yizhi (Biomed Opt Express, 2018)
Optical-resolution photoacoustic microscopy (OR-PAM) images biological tissue with sub-cellular resolution and optical absorption contrast. OR-PAM is limited by the tradeoff among imaging speed, field of view, and sensitivity. In this work, we present an OR-PAM technique based on an unfocused side-looking fiber optic ultrasound (FOUS) sensor, which achieves high imaging speed, large field of view, and good sensitivity for in vivo imaging. The FOUS sensor is developed based on a dual-polarized fiber laser and read out with real-time frequency demodulation. Via minimizing the readout noise, the sensor offers a noise-equivalent pressure of 43.6 Pa, enabling high detection sensitivity over a large field of view. High imaging speed is achieved via scanning the laser beam with a 2D galvo mirror in the ultrasound detection area. Microvascular imaging with a frame rate of 2 Hz over a 2 × 2 mm(2) area has been demonstrated in the mouse ear. The new OR-PAM technique may be used in the visualization of biological and physiologic dynamics.